Students’ Opinions about Blended Learning in Redox Material and Compounds Nomenclature - Susilaningsih, Endang; Musyarofah, Musyarofah (Jurnal Penelitian Pendidikan, 2020)
This study aims to determine the response of learners to Blended learning models - Problem Based Learning. The method used is pre experimental design. The sample in this study was the students of class X SMA Negeri 1 Ungaran and SMA Negeri 2 Ungaran, amounting to 143 learners. To study the response of the students to use the questionnaire. Learners' questionnaire responses were analyzed descriptively by calculating the average of each aspect. Likert Scale questionnaire was analyzed by being converted into a quantitative scale. Item statement consists of a positive statement which amounts to 15. The questionnaire was given to the students after participating in the learning process with a model Blended- Problem Based Learning. The results showed that the students responded positively to the model developed, indicating the learning model Problem Based Learning Blended- very useful to help learners to understand the concept of redox and nomenclature of chemical compounds. In addition to understanding the concept, Blended-Problem Based Learning also help learners to solve problems in everyday life associated with redox material and nomenclature of chemical compounds.